Design of a reactive control based autonomous mobile robot - Kho, Mark Jannson L. (Animo Repository, 2002)
The ability of an autonomous mobile robot to react instantaneously to stimuli from its environment does not only depend on the actuators and sensors used but it is more dependent on the type of control architecture used by the robot. This study involves the development and fabrication of a differential drive wheeled mobile robot, which was used to test the reactive control system. The reactive control system involves several independent tasks running in parallel and a coordinating system that arbitrates which task be the emergent task. The robot was initially programmed with a low level task of wandering , and since tasks are independent from each other, additional tasks such as obstacle avoidance, light seeking and line following were added without altering the other tasks. The robot was also tested with the traditional Sense-Plan-Act (SPA) architecture using the same tasks running in series. The result of implementing a reactive controller was a more responsive robot and more flexible architecture compared to a robot built with the traditional architecture.